CELLULOSIC SUBSTRATES FOR REMOVAL OF POLLUTANTS FROM AQUEOUS SYSTEMS: A REVIEW. 1. METALS - Martin A. Hubbe; Syed Hadi Hasan; Joel J. Ducoste (BioResources, 2011)
Recent years have seen explosive growth in research concerning the use of cellulosic materials, either in their as-recieved state or as modified products, for the removal of heavy metal ions from dilute aqueous solutions. Despite highly promising reports of progress in this area, important questions remain. For instance, it has not been clearly established whether knowledge about the composition and structure of the bioadsorbent raw material is equally important to its availability at its point of use. Various physical and chemical modifications of biomass have been shown to boost the ability of the cellulose-based material to bind various metal ions. Systems of data analysis and mechanistic models are described. There is a continuing need to explain the mechanisms of these approaches and to determine the most effective treatments. Finally, the article probes areas where more research is urgently needed. For example, life cycle analysis studies are needed, comparing the use of renewable biosorbents vs. conventional means of removing toxic metal ions from water.